IMPACT OF MARKET LIQUIDITY AND INFORMATION DEMAND ON HERDING BEHAVIOR PRE AND POST COVID PERIOD:EVIDENCE FROM PAKISTAN STOCK MARKET (Contemporary Journal of Social Science Review, 2025)
The main objective is to study herding behavior changes throughout different times in the COVID-19 pandemic. In addition, this research seeks to examine how investors’ herding actions depend on market liquidity and the amount of information being searched for. For this study, we utilize daily stock closing prices of 30 firms from the Pakistan Stock Exchange between 2018 and 2024 to examine herding behavior. We found that changing our investment strategy from herding had negative results, even though the theory predicts high returns. The failure of the study uncovered a more detailed truth than anticipated. There are moments when the crowd’s enthusiasm causes prices to rise without being supported by important reasons. Because people can change their actions rapidly, a crowd’s behavior may turn negative, resulting in lower returns. Don’t only count on the hot stocks, since choosing them hastily can be dangerous. To invest wisely, you need to know the market well and what affects it, rather than being caught up in what others do. The findings suggest ways that help investors, policymakers, and researchers during the COVID-19 crisis. The frequent failures seen in the market are due to a mix of poor market sentiment, overwhelming news, illiquid markets, the state of the economy, and risky trading. As a result of these activities, market activity decreases, and outcomes become negative.